Analysis of shotcrete lining of underground tunnels - Ghiasi, Vahed; Omar, Husaini (Universiti Putra Malaysia Press, 2011)
Shotcrete is a process where concrete is projected or "shot" under pressure, using a feeder or a "gun" onto a surface to form structural shapes including walls, floors, and roofs. The surface can be wood, steel, polystyrene, or any other surfaces that concrete can be projected onto. The surface can be trowel led smooth while the concrete is still wet. Shotcrete has high strength, durability, low permeability, excellent bond, and limitless shape possibilities. These properties allow shotcrete to be used as a structural material in most cases. Although the hardened properties of shotcrete are similar to conventional cast-in-place concrete, the nature of the placement process provides additional benefits, such as excellent bond with most substrates and instant or rapid capabilities, particularly on complex forms or shapes. In addition to building homes, shotcrete can also be used to build pools. The practice of underground tunneling shows that the degree of stability of tunnels is dependent on the state of the soil, rock mass, and shotcrete around the tunnel contour. The development in the urban or suburban areas leads to the construction of tunnels in all kinds of soil and rock. Meanwhile, the construction of tunnels in shallow depth or soft soils causes the ground to displace. The determination of soil and rock mechanical properties to assess the stability of New Austrian Tunnelling Method (NATM) tunnels and design the support system is one of the most important steps in tunnelling. This paper provides information pertaining to the safety and increase the stability of NATM tunnel before, during and after the operation of the tunnel. Therefore, the shotcrete process is a recognized method for cemented sandy silt stabilization, with the aid of high pressure shot concrete to increase the stability of tunnels.